Psychoeducational Teaching in Islamic Religious Education Learning: A Solution to Overcoming Toxic Culture Among Students - Ulfah; Hamdanah; Surawan (Ta'dib, 2025)
The purpose of this study is to analyze and identify the role of Islamic Religious Education (PAI) subject teachers in overcoming toxic culture that develops in the student environment, providing positive values to students by guiding students towards academic success, personal growth, and future readiness. This study focuses on the methods used by PAI teachers to overcome Toxic Culture and how the application of PAI Psychoeducation Teaching as an effort to overcome toxic culture is considered important to prevent toxic culture in students. This research uses descriptive qualitative research with data collection techniques in the form of in-depth interviews, observations and surveys. The subjects of this research were 3 PAI teachers and students at SMK Karsa Mulya. The results of this study indicate that Psychoeducational Teaching conducted by PAI teachers is very effective (94.93%) as an effort to overcome toxic culture in students. The methods used were dialogical methods and project-based learning methods, while the aspects of psychoeducational teaching implementation included group counseling sessions, integration of teaching materials with social issues, and evaluation and feedback.